2021
DOI: 10.3390/plants10061203
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Lighting and High Daily Light Integral Enhance Yield and Quality of Mass-Produced Nasturtium (Tropaeolum majus L.) in Plant Factories

Abstract: Nasturtium (Tropaeolum majus L.), as a medicinal plant, has a high phenolic content in its leaves and flowers. It is often used in salads as a dietary vegetable. Attracting strong demand, it could be a good candidate crop for a plant factory with artificial lighting (PFAL) that can achieve the mass production of high-quality crops with high productivity by regulating environmental conditions such as light. In this study, two experiments were conducted to investigate the effects of continuous lighting (CL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Water use efficiency of photosynthesis (WUE Pn ) was calculated as WUE Pn = Gs ÷ P n [41]. The youngest fully expanded leaf from each treatment was used for measurements [42]. Eight samples were measured from each treatment.…”
Section: Gas-exchange Parametersmentioning
confidence: 99%
“…Water use efficiency of photosynthesis (WUE Pn ) was calculated as WUE Pn = Gs ÷ P n [41]. The youngest fully expanded leaf from each treatment was used for measurements [42]. Eight samples were measured from each treatment.…”
Section: Gas-exchange Parametersmentioning
confidence: 99%
“…It is necessary to carefully use the RUE definitions in PFALs. Some studies used g mol −1 as the unit of RUE and calculated it based on the sum of PAR on the cultivation area or irradiation by lamps, which focused on the production efficiency rather than the physiological mechanisms [73][74][75]. Recently, a few studies have defined RUE based on the cumulative incident radiation on the PLA [10,76,77].…”
Section: Rue Of Canopymentioning
confidence: 99%
“…Furthermore, under the same DLI, CL (L3) with lower PPFD had lower productivity compared to L2 and L4 conditions which had higher PPFDs but shorter photoperiods. Controversial results such as CL promoted growth were reported in lettuce ( Zha et al., 2019 ), medicinal plant, Nasturtium ( Xu et al., 2021 ) and rocket plants ( Proietti et al. (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…This result implies that CL may increase nitrate reductase activity (NRA) and the reduction of ( Proietti et al., 2021 ). In the study of medicinal plant, Nasturtium ( Tropaeolum majus L.) under the same DLI but different photoperiods with different PPFDs, Xu et al. (2021) found that leaf biomass, concentrations of secondary metabolites, and light use efficiency increased under the CL compared to the 16-h treatment.…”
Section: Introductionmentioning
confidence: 99%